Who Benefits from Firm Success? Heterogenous Rent Sharing in New Zealand - Corey Allan; David C. Maré (Institute of Labor Economics (IZA), 2022)
We examine heterogeneous rent-sharing in New Zealand using LEED data. Using a refined measures of quasi-rents per worker, we find that 20% to 30% of workers are in zero-excess-rent firms - disproportionately women, Māori or Pacific peoples, low-qualified workers, and those in hospitality, admin services, and retail industries,. The overall rent-sharing elasticity of 0.03 is equivalent to 38 higher earnings per 1,000 of excess rents per worker. Sharing varies by qualification, tenure, and ethnicity, but not by firm size or age. In most industries, workers receive 1,500-2,000 of rents per year. Sharing is highest in auxiliary finance and professional services sectors and lowest in grocery retailing, food and beverage manufacturing and utilities. There is some evidence of insurance-type behaviour by firms. Differences in bargaining power are also likely to affect rent sharing variation.
Keywords: J31; J71; J10; D22; 330; wage determination; rent-sharing; imperfect competition